2021
DOI: 10.1111/ajt.16762
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperoxaluria diagnosed after kidney transplant: A review of the literature and case report of aggressive renal replacement therapy and lumasiran to prevent allograft loss

Abstract: Primary hyperoxaluria type 1 is a rare inherited disorder caused by abnormal liver glyoxalate metabolism leading to overproduction of oxalate, progressive kidney disease, and systemic oxalosis. While the disorder typically presents with nephrocalcinosis, recurrent nephrolithiasis, and/or early chronic kidney disease, the diagnosis is occasionally missed until it recurs after kidney transplant. Allograft outcomes in these cases are typically very poor, often with early graft loss. Here we present the case of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…37 More recently, in a young patient diagnosed with PH1 following a kidney transplant, graft kidney function stabilized following lumasiran and aggressive kidney replacement therapy, allowing for discontinuation of dialysis. 38 The challenge the community J o u r n a l P r e -p r o o f now faces is to understand what might be a suitable POx level at which kidney-only transplant could be considered for patients with PH1, acknowledging that such a decision would not rely on a POx level alone. POx levels may fluctuate during follow-up, unrelated to changes in serum creatinine or eGFR 39 ; in addition, there is poor agreement in POx values between laboratories.…”
Section: Illuminate-c Evaluated the Efficacy And Safety Of Lumasiran ...mentioning
confidence: 99%
“…37 More recently, in a young patient diagnosed with PH1 following a kidney transplant, graft kidney function stabilized following lumasiran and aggressive kidney replacement therapy, allowing for discontinuation of dialysis. 38 The challenge the community J o u r n a l P r e -p r o o f now faces is to understand what might be a suitable POx level at which kidney-only transplant could be considered for patients with PH1, acknowledging that such a decision would not rely on a POx level alone. POx levels may fluctuate during follow-up, unrelated to changes in serum creatinine or eGFR 39 ; in addition, there is poor agreement in POx values between laboratories.…”
Section: Illuminate-c Evaluated the Efficacy And Safety Of Lumasiran ...mentioning
confidence: 99%
“…So far, experiences with Oxlumo ® treatment (outside long-term studies from the company itself) have been reported only in ten PH1 cases, both children (n = 7) [85][86][87][88] and adults (n = 3) [89-91] (Table 3) with the time under treatment reported as from 1 to 18 months. Good tolerance, reduced urinary oxalate/creatinine ratio, and stability (or even slight improvement) of renal function were reported only in the children treated.…”
Section: Substrate Reduction Therapies: the Expensive Approachmentioning
confidence: 99%
“…Glycolate values (in urine or plasma) were not provided in any case. In one case, however, metabolic acidosis was reported during a 5-month administration period (measured by low HCO 3 − values and negative base excess) and treatment with sodium bicarbonate was needed [ 88 ]. Here, we may speculate that acidosis might possibly be due to very high plasma glycolic acid levels (Table 3 ).…”
Section: Current Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed graft function caused by the deposition of oxalate in allograft is easily misdiagnosed as acute rejection and needs kidney biopsy for accurate diagnosis. For this reason, a high index of suspicion for the diagnosis of PH is very important in patients with CKD and/or ESRD with uncertain etiology especially accomplished with nephrocalcinosis or nephrolithiasis (13). Such patients need exact preoperative screening for PH and proper treatment in both kidneys before KTx (13).…”
Section: Primary Hyperoxaluriamentioning
confidence: 99%